Surface nitridation of Li4Ti5O12 by thermal decomposition of urea to improve quick charging capability of lithium ion batteries - Jihyun Jang (Scientific Reports, 2021)
Abstract As the application of lithium-ion batteries in electric vehicles increases, the demand for improved charging characteristics of batteries is also increasing. Lithium titanium oxide (Li4Ti5O12, LTO) is a negative electrode material with high rate characteristics, but further improvement in rate characteristics is needed for achieving the quick-charging performance required by electric vehicle markets. In this study, the surface of LTO was coated with a titanium nitride (TiN) layer using urea and an autogenic reactor, and electrochemical performance was improved (initial Coulombic efficiency and the rate capability were improved from 95.6 to 4.4% for pristine LTO to 98.5% and 53.3% for urea-assisted TiN-coated LTO, respectively. We developed a process for commercial production of surface coatings using eco-friendly material to further enhance the charging performance of LTO owing to high electronic conductivity of TiN.